Rationing and Rent Dissipation in the Presence of Heterogeneous Individuals - Suen, Wing (Journal of Political Economy, 1989)
This paper discusses the implications of rationing by waiting when consumers have different time costs and personal valuations. The joint distribution function of time costs and personal valuations is used to characterize market equilibrium. It is argued that, under certain conditions, an increase in the variance of time costs will reduce the dissipation of rent. Furthermore, it is shown that introducing a secondary market for a rationed good does not necessarily improve welfare because total surplus under rationing by waiting depends more on the variance than on the level of time costs and personal valuations. The model is also used to discuss other institutions that involve rent-seeking activities, such as the patent system and import quotas.